The Influence of Adult Attachment on Rejection Sensitivity with Self-Esteem as a Mediator in College Students - Putri Hannanisa; Rinaldi (INDONESIAN COUNSELING AND PSYCHOLOGY, 2026)
This study aims to determine the effect of adult attachment on rejection sensitivity, with self-esteem as a mediator in college students currently in romantic relationships. The research method used a quantitative approach with a correlational design. The sample consisted of 156 college students aged 18–25 who had been in a romantic relationship for at least six months and were selected through quota sampling. Data were collected using the Adult Rejection Sensitivity Questionnaire (ARSQ), Experiences in Close Relationships-Revised (ECR-R), and the Rosenberg Self-Esteem Scale (RSES). The A-RSQ consists of interpersonal scenarios with two items for each situation: anxiety about rejection and expectations of acceptance, each with a 6-point Likert scale. The ECR-R uses a 7-point Likert scale ranging from strongly agree to strongly disagree to measure the anxiety and avoidance dimensions of attachment. The RSES uses a 4-point Likert scale ranging from strongly agree to strongly disagree to measure individual self-esteem. Data analysis was conducted through prerequisite analysis tests, normality tests, linearity tests, multicollinearity tests, and path analysis to examine the direct and indirect effects between variables. The results showed that avoidant attachment had a significant direct effect on rejection sensitivity, while anxiety attachment did not show a significant direct effect. Self-esteem had a significant negative effect on rejection sensitivity and mediated the relationship between anxiety attachment and rejection sensitivity, but did not mediate the relationship between avoidant attachment and rejection sensitivity. These findings emphasize the important role of self-evaluation in the dynamics of romantic relationships in early adulthood, especially in understanding sensitivity to rejection. This study provides implications for the development of psychological interventions aimed at improving self-esteem and the quality of interpersonal relationships in college students.